Management of chyle leaks following esophageal resection: a systematic review. Issue 11 (16th March 2021) - Power, Robert; Smyth, Philip; Donlon, Noel E; Nugent, Timothy; Donohoe, Claire L; Reynolds, John V
Summary: Background: Chyle leakage is an uncommon but potentially life-threatening complication following esophageal resections. The optimal management strategy is not clear, with a limited evidence base. Methods: Searches were conducted up to 31 December 2020 on MEDLINE, Embase, and Web of Science for randomized trials or retrospective studies that evaluated the management of chyle leakage following esophageal resection. Two authors independently screened studies, extracted data, and assessed for bias. The protocol was prospectively registered on PROSPERO (CRD: 42021224895) and reported in accordance with preferred reporting items for systematic reviews and meta-analyses guidelines. Results: A total of 530 citations were reviewed. Twenty-five studies, totaling 1016 patients met the inclusion criteria, including two low-quality clinical trials and 23 retrospective case series. Heterogeneity of study design and outcomes prevented meta-analysis. The overall incidence of chyle leak/fistula was 3.2%. Eighteen studies describe management of chyle leaks conservatively, 17 by surgical ligation of the thoracic duct, 5 by pleurodesis, and 6 described percutaneous lymphangiography with thoracic duct embolization or disruption. Conclusions: The evidence base for optimal management of chyle leakage postesophagectomy is lacking, which may be related to its low incidence. There is a paucity of high-quality prospective studies directly comparing treatment modalities, but there is some low-certainty evidence that percutaneous approaches have reduced morbidity but lower efficacy compared with surgery. Further high-quality, prospective studies that compare interventions at different levels of severity are needed to determine the optimal approach to treatment.